Barring Freedom: Art, Abolition and the Museum in Pandemic Times. (1st April 2022) - Moore, Alexandra; Nelson, Rachel
Barring Freedom, a travelling exhibition featuring artworks engaging the histories and current conditions of prisons and policing in the United States, was to open in April 2020. While COVID-19 disrupted that plan, the realities of inequity in the United States placed into stark relief by the pandemic and the uprisings of summer 2020 brought urgency to rethinking the curatorial vision of the exhibition to reach audiences beyond the gallery walls. Buoyed by the idea that, in the words of Angela Davis, art can 'propel people towards social emancipation', the exhibition and related programming was reconceived as an ongoing, interdisciplinary, public scholarship initiative reaching across the borders normally perceived between museums, prisons and universities. Opportunities arose for expanded forms of community building and participation that welcomed different forms of knowledge, furthering the political and aesthetic aims of the project to shift the social attachment to prisons.